ANALYSIS OF SEMASIOLOGICAL-STYLISTIC DEVICES IN THE GREEN DOOR BY O.HENRY - Mulkijakhon Gulyamova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article aims at analyzing application of stylistic devices in literature as an example of a short story “The Green Door” by O.Henry. The formative features, such as description of characters, setting, feelings and thoughts of bodies, are considered thoroughly with a view to acquire better comprehension of deep notions of the literary work. The stylistic analyze of the short story covers an array of stylistic categories, namely phonetical stylistic devices (annotation, alliteration, consonance, rhyme), lexical stylistic devices (parallelism, repitation) and semasiological stylistic devices (simile, synecdoche, personification, hyperbole). Finally, deductions on focused items are provided after extensive discussions.